Comparison of the Effects of Electrolytic and Chemical Destruction of the Red Nucleus on the Compensatory Capacity of Rats With Rubrospinal Tract Lesions - V. V. Fanardjian; E. V. Papoyan; V. I. Pogossian; O. V. Gevorkyan (Neural Plasticity)
Transection of the rubrospinal tract in rats, performed before lesion of the red nucleus, resulted in the facilitated recovery of motor activity and operantly conditioned reflexes. Such facilitation was absent when the red nucleus is lesioned alone. This phenomenon is explained by the switching of descending influences on the corticospinal tract through the participation of the following system: red nucleus—inferior olive—cerebellum—ventrolateral thalamic nucleus—cerebral cortex. The above mentioned facilitating influence on the recovery process was particularly prominent in rats with quinolinic acid-induced lesion of the red nucleus. Under these conditions, the cerebellar ascending fibers to the ventrolateral thalamic nucleus were preserved. Decreased facilitated recovery following electrolytic lesion of the red nucleus suggests the existence of additional cerebello-cortical pathways for the realization of the switching phenomenon.